2002
DOI: 10.1046/j.1365-2958.2002.03171.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of Pseudomonas aeruginosa 1244 pilin: glycan substrate specificity

Abstract: SummaryThe structural similarity between the pilin glycan and the O-antigen of Pseudomonas aeruginosa 1244 suggested that they have a common metabolic origin. Mutants of this organism lacking functional wbpM or wbpL genes synthesized no O-antigen and produced only non-glycosylated pilin. Complementation with plasmids containing functional wbpM or wbpL genes fully restored the ability to produce both O-antigen and glycosylated pilin. Expression of a cosmid clone containing the O-antigen biosynthetic gene cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 72 publications
(87 reference statements)
4
86
0
Order By: Relevance
“…This study in combination with detailed microscopic investigations in our laboratory 4 revealed that the cell surface architecture of T. forsythia is so far unique, with a typical Gramnegative cell envelope profile being overlaid with an ϳ22-nmthick, closed, monolayer that is formed by co-assembly of the two T. forsythia S-layer glycoproteins. Whereas the TfsA and TsfB S-layer protein portions are antigenically diverse according to immunoblot evidence, 4 identical oligosaccharides are displayed at multiple sites on either S-layer protein via O-glycosidic linkage units between ␣-D-Galp and Thr and Ser residues, respectively, that are scattered over the whole S-layer proteins.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…This study in combination with detailed microscopic investigations in our laboratory 4 revealed that the cell surface architecture of T. forsythia is so far unique, with a typical Gramnegative cell envelope profile being overlaid with an ϳ22-nmthick, closed, monolayer that is formed by co-assembly of the two T. forsythia S-layer glycoproteins. Whereas the TfsA and TsfB S-layer protein portions are antigenically diverse according to immunoblot evidence, 4 identical oligosaccharides are displayed at multiple sites on either S-layer protein via O-glycosidic linkage units between ␣-D-Galp and Thr and Ser residues, respectively, that are scattered over the whole S-layer proteins.…”
Section: Discussionmentioning
confidence: 73%
“…Whereas the TfsA and TsfB S-layer protein portions are antigenically diverse according to immunoblot evidence, 4 identical oligosaccharides are displayed at multiple sites on either S-layer protein via O-glycosidic linkage units between ␣-D-Galp and Thr and Ser residues, respectively, that are scattered over the whole S-layer proteins. According to combined 600.13-MHz 1 H NMR/LC-ESI-MS approaches, the T. forsythia S-layer oligosaccharide is an overall highly diverse and branched structure containing several modified glycose residues (compare with Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This relaxed specificity is in contrast to the typical eukaryotic OST, where a terminal ␣1-2-linked glucose residue is of central importance for efficient glycosylation (28). Interestingly, it has been reported that the sugars transferred during pilin O glycosylation in P. aeruginosa are products of the O antigen biosynthetic pathway and that the process occurs with low glycan substrate specificity (22). Because O antigen polymerization takes place at the periplasmic side of the inner membrane (17), the efficient transfer of O polysaccharide to proteins by PglB confirmed that N-glycosylation in bacteria takes place in the periplasm.…”
Section: Discussionmentioning
confidence: 92%
“…Pseudomonas aeruginosa O11 (6,22,23) and the corresponding empty vector control pLAFR1 were kindly provided by Peter Castric (Duquesne University, Pittsburgh). The strains and plasmids used are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%